Young Learners: An Examination of the Psychometric Properties of the Early Literacy Knowledge and Skills Instrument. (October 2015) - Chan, Man Ching Esther
The Early Literacy Knowledge and Skills (ELKS) instrument was informed by the work of Ferreiro and Teberosky based on the notion that young children could be differentiated according to levels of sophistication in their understanding of the rules of written language. As an initial step to evaluate the instrument for teaching purposes, the present study examines its psychometric properties in terms of internal consistency reliability, model-data fit, item discrimination, match between item difficulty and ability range in the sample, and item difficulty according to Ferreiro and Teberosky's theory of early literacy development. Overall, the ELKS instrument showed good psychometric properties in these areas, although two items in particular may require further investigation and possible revision according to the model-data fit index. Future directions to investigate the potential classroom application of the instrument are suggested.